2012
DOI: 10.1063/1.4714614
|View full text |Cite
|
Sign up to set email alerts
|

Drift wave dispersion relation for arbitrarily collisional plasma

Abstract: The standard local linear analysis of drift waves in a plasma slab is generalized to be valid for arbitrarily collisional electrons by considering the electrons to be governed by the drift-kinetic equation with a BGK-like (Bhatnagar-Gross-Krook) collision operator. The obtained dispersion relation reduces to that found from collisionless kinetic theory when the collision frequency is zero. Electron temperature fluctuations must be retained in the standard fluid analysis in order to obtain good quantitative agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 11 publications
1
32
0
Order By: Relevance
“…It is unrealistic to expect that this assumption holds in the tokamak SOL where less mobile ions are naturally hotter than electrons [13]. Some recent modeling work addressed the effect of finite T i,fil [14,15] and have shown that, for example, the growth rate of linear drift waves decreases moderately and the convective rate of filaments increases as T i,fil becomes larger than T e,fil . Further progress in addressing finite ion temperature effects is partly impeded by a lack of T i,fil measurements.…”
Section: Ion Energies In Turbulent Plasma Filamentsmentioning
confidence: 99%
“…It is unrealistic to expect that this assumption holds in the tokamak SOL where less mobile ions are naturally hotter than electrons [13]. Some recent modeling work addressed the effect of finite T i,fil [14,15] and have shown that, for example, the growth rate of linear drift waves decreases moderately and the convective rate of filaments increases as T i,fil becomes larger than T e,fil . Further progress in addressing finite ion temperature effects is partly impeded by a lack of T i,fil measurements.…”
Section: Ion Energies In Turbulent Plasma Filamentsmentioning
confidence: 99%
“…The first fully 3D studies of plasma blobs have recently been examined theoretically and numerically by Angus et al [4][5][6][7][8] The main result of these works is that, for parameters typical of current and future tokamaks, the 3D drift wave instability can dissipate plasma blobs on time scales short compared to their convective motion.…”
Section: Introductionmentioning
confidence: 98%
“…Almost all of the works on plasma blobs (including the previous 3D studies [4][5][6][7][8] have used a reduced vorticity in their studies. Some exceptions are the 2D studies in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…In the interchange mechanism the main role of hot ions is to increase the pressure of the plasma which enhances the drive for the interchange motion, but does not change the motion itself. When 3D effects are important hot ions can affect the stability of resistive drift waves [45], though the effect is not significant and certainly does not alter the basic mechanism behind the resistive drift wave. The inclusion of hot ions is therefore not essential to modelling filament motion and consequently has been neglected here.…”
Section: Governing Equationsmentioning
confidence: 99%